MRI and CT of the Female Pelvis - Hamm, Bernd; Forstner, Rosemarie (Diagnostic Imaging,, 2007)
MRI and CT exquisitely depict the anatomy of the female pelvis and offer fascinating diagnostic possibilities in women with pelvic disorders. This volume provides a comprehensive account of the use of these cross-sectional imaging techniques to identify and characterize developmental anomalies and acquired diseases of the female genital tract. Both benign and malignant diseases are considered in depth, and detailed attention is also paid to normal anatomical findings and variants. Further individual chapters focus on the patient with pelvic pain and the use of MRI for pelvimetry during pregnancy and the evaluation of fertility. Throughout, emphasis is placed on the most recent diagnostic and technical advances, and the text is complemented by many detailed and informative illustrations. All of the authors are acknowledged experts in diagnostic imaging of the female pelvis, and the volume will prove an invaluable aid to everyone with an interest in this field.